Hibiscus cannabinus L. leaf and seed in cosmetic formulation: an integrated approach as antioxidant and melanogenesis inhibitor - Sim, Yan Yi; Tan, Chin Ping; Cheong, Ling Zhi; Nyam, Kar Lin (Elsevier, 2022)
Excessive exposures to UV radiation can caused skin hyperpigmentation and lead to oxidative damage that compromise the integrity of the skin. The application of cosmeceuticals products is reported as an effective strategy. In the last decades, sustainability arises as a challenge, and the cosmetic industry is not an exception. The explore for new sustainable natural active ingredients with multifunctional properties has emerged as a novel concept. The in vitro antioxidant and depigmenting properties of the purified kenaf leaves extracts (PKLE) were first assessed in this study by the antioxidant and antityrosinase activity. The protective effect against oxidative stress and inhibitory effect on melanogenesis of PKEL and kenaf seed oil (KSO) incorporated lotion (KLEL) was further assessed in normal human dermal fibroblast (NHDF) and epidermal melanocytes (NHEM). PKLE showed high antioxidant content and free radical scavenging activity, strong competitive inhibitory effect against mushroom tyrosinase activity, and demonstrated robust copper chelating ability. While for KLEL, it can significantly suppress the hydrogen peroxide induced oxidative stress in NHDF. Additionally, KLEL demonstrated comparable effect with the positive control in downregulating the melanin pigments production and cellular tyrosinase activity. KLEL can also shorten dendrites generation in NHEM. Besides, it demonstrated that KLEL can suppress the tyrosinase (TYR), tyrosinase-related protein 1 (TYP-1), and tyrosinase-related protein 2 (TYP-2), and microphthalmia-associated transcription factor (MITF) gene and protein expression. These findings support the KLEL formulated with the kenaf leaf and seed as sustainable sources of novel cosmetic active ingredients with antioxidant properties and therapeutic potential in skin hyperpigmentation.